Ump undergraduates took part in the 451th Asean day celebration - UMP, PNC

(untitled)
Universiti Malaysia Pahang (UMP) and the information Department jointly organised the 45th Asean Day celebration with the theme 'One Community One Purpose', aimed at echancing public understanding and participation relating to Asean - a grouping comprising Brunei, the Philippines, Indonesia, Cambodia, Laos, Myanmar, Singapore, Thailand, Vietnam and Malaysia.